If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13d + 4 = 5d + 52 Reorder the terms: 4 + 13d = 5d + 52 Reorder the terms: 4 + 13d = 52 + 5d Solving 4 + 13d = 52 + 5d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-5d' to each side of the equation. 4 + 13d + -5d = 52 + 5d + -5d Combine like terms: 13d + -5d = 8d 4 + 8d = 52 + 5d + -5d Combine like terms: 5d + -5d = 0 4 + 8d = 52 + 0 4 + 8d = 52 Add '-4' to each side of the equation. 4 + -4 + 8d = 52 + -4 Combine like terms: 4 + -4 = 0 0 + 8d = 52 + -4 8d = 52 + -4 Combine like terms: 52 + -4 = 48 8d = 48 Divide each side by '8'. d = 6 Simplifying d = 6
| 73-6x=31 | | 5(x-5)=7.2 | | 3x+9=44 | | -3=-3t-12 | | 6(a+1)=30.6 | | 2u^2-2u-1=0 | | 29.8=4c-5 | | 4e-2=28.4 | | 7p=11.9 | | 56.25=2x^2+y^2 | | 6(x-9)=0 | | p=0.1x^2 | | (x+1).3=(x-2).2 | | 2(a+9)=26 | | p=2X | | 4x+4=3x+5 | | x+4=2x-7 | | (3u^2+2u-1)-(-6u^2+2u+2)+(6u^2+9u+2)= | | 3x-1=7-4(6-2x) | | 6(t+-2)-76=142 | | -5(r-3)-2(2r+1)=-8 | | 4(2b+3)=-3(b-1)+20 | | 36+7.1=2.5b+11.5 | | 4-5x=2x+1 | | 5x+6=3x-6 | | 16t+7=19t+2 | | x^4-8x^2+14=0 | | =300x^2-12 | | 5x+500=7x+200 | | 2x=4-3(x-2) | | 7x+200=5x+500 | | 5t-10= |